The Dialogue of Ḥikma: Generating Harmony in Muslim-Non-Muslim Relations - Suraya Sintang (Islam and Christian-Muslim relations, 2013)
This article seeks to explain the concept of the dialogue of ḥikma as a qur'anic principle in developing harmony in Muslim-non-Muslim relations. Living together harmoniously is essential in a community made up of a myriad of cultures and religions. Efforts to create harmony can be realized through the dialogue of ḥikma and by inculcating it as the culture in daily life interaction. This is truly essential in the context of mixed-faith families. In order to explore how the dialogue of ḥikma can be applied in Muslim-non-Muslim relations, this article examines the experience of Muslim converts living together with their non-Muslim families of origin. The research was conducted through in-depth interviews with selected Muslim converts from a variety of cultural backgrounds, living in the area of Kota Kinabalu, Sabah. The results indicate that Muslim converts share similar experiences in applying the dialogue of ḥikma as a mechanism for solving family problem arising as a result of conversion to Islam.